Lizard visual ecology - Fleishman, Leo J. (Frontiers in Amphibian and Reptile Science, 2024)
Visual ecology is the study of how visual systems are evolutionarily adapted to the light conditions animals experience and the visual tasks they must perform. The greatest progress in this field has been made in studies of aquatic systems. Our understanding of the influence of how different terrestrial habitats have shaped the evolution of visual physiology and anatomy is more limited. Lizards are an excellent model system for examining terrestrial visual ecology because in most cases, each species experiences a limited range of habitat light conditions and these differ among species. Some aspects of visual physiology and anatomy have evolved in response to habitat conditions, while others are widely shared by a great diversity of species, suggesting that their features are largely inherited and have changed very little through evolutionary time. Understanding which features have evolved as specializations to current conditions and which are inherited and largely unchanged is critical to understanding the role that visual ecology plays in shaping behavior. In this article I review some basic features of the lizard visual system, including the processes by which lizards estimate distance and depth. I then explore the evolutionary response (or lack thereof) to differences in habitat structure, light intensity and spectral quality. I also explore some relationships between lizard color patterns and their color perception. The phylogenetic range of species that have been studied is small, and many key aspects of behavior have received relatively little attention. These are potentially rich areas for future study.